Do millennials pay attention to corporate~social responsibility in comparison to previous generations? Are they motivated to lead in times of transformation? A qualitative review of generations, CSR and work motivation - Susanne Rank; Francoise Contreras (International Journal of Corporate Social Responsibility (JCSR), 2021)
The purpose of this qualitative review is to analyze empirical studies on whether the existing generations differ in their work beliefs, i.e. in their internal CSR perceptions and their leadership motivation, especially Generation Y (born after 1980), in contrast to previous generations. According to the literature review, there is some evidence demonstrating that Generation Y is slightly different from the preceding Generation X in their work beliefs in some internal CSR features. However, this generation is not as special as suggested in popular media. As most research is conducted in the USA and Europe, as well as a few studies in Asia and Africa, the necessity of conducting more empirical research in different cultures is highlighted. The research outlook shows important implications for human resource management (HRM) as to whether HRM needs to handle employees differently across generations, or a general change in work values is occurring in this disruptive twenty-first century.
Keywords: 650; Generation work values; Corporate social responsibility; Leadership motivation; Generational diversity at workplace; Affective commitment